Phlebotomine sand flies (Diptera: Psychodidae) of Chiapas collected near the Guatemala border, with additions to the fauna of Mexico and a new subgenus name - Ibañez Bernal, Sergio (2015)
Collections from four localities, two of the High Plateau and two of the Eastern Mountains Municipality of Chiapas, near the border with Guatemala, included 26 species with four new species records for Mexico: Lutzomyia (Helcocyrtomyia) hartmanni (Fairchild & Hertig, 1957), Dampfomyia (Coromyia) disneyi (Williams, 1987), Psychodopygus bispinosus (Fairchild & Hertig, 1951), and Psychodopygus corossoniensis (LePont & Pajot, 1978). These records represent an updated total of 50 species in Mexico, 48 of which are extant species and the remaining two fossils. The name Xiphopsathyromyia n. n. is proposed in substitution of Xiphomyia Artemiev, 1991, a homonym of Xiphomyia Townsend, 1917, a genus of Tachinidae (Diptera).